하이브리드텍스트의 표현과 의미전달과정에 관한 연구 - 김영호; Young Ho Kim (기초조형학연구, 2015)
본 연구는 시각커뮤니케이션 디자인에 있어서 하이브리드텍스트의 표현과 의미전달과정을 분석함으로써 인간커뮤니케이션을 이해하고 이와 더불어 커뮤니케이션디자인에서 하이브리드텍스트의 입지를 정립하고자 하였다. 하이브리드텍스트는 다중의 감각과 기호 그리고 다중매체의 결합으로 생성되는 인간커뮤니케이션의 총체적 수단으로 단순한 의미의 전달만이 아닌 생산주체의 경험과 사고를 공유할 수 있는 최적의 조건을 제공한다. 이러한 하이브리드텍스트는 일반형, 잠복형, 변이형의 3 가지 표현 유형을 가지며 감각을 통한 각 매체들의 통합을 활용한 사실적이고 즉시적재현 커뮤니케이션을 추구함으로써 의미전달에 있어 현장성을 확보한다. 하이브리드텍스트에 대한 관심과 연구는 인간의 감각을 통한 조형적 경험과 주체의 지식에 근거하는 의미론적 체계를 동시에 탐구하게 하는 학문적 대상인 동시에 다양한 전공 분야와의 학제간 연구로 이어질 수 있는 교량적 위치로서의 역할을 수행할 수 있다. 그리고 디자인 교육에 있어서 다양한 학문과 기호체계 그리고 매체에 대한 하이브리드텍스트의 연구는 디지털미디어 리터러시를 통한인간을 이해하고 인간을 위한 디자인의 개발을 위한 제도적 기틀 마련에 기여할 수 있을 것이다. This paper analyzes the expression and delivery of meaning in hybrid text in terms of visual communication design to further our understanding of human communication processes. At the same time, the present paper confirms the position of hybrid text in the field of design in order to suggest a new direction for design education in the digital environment. As a method of human communication created through the composition of synesthesia, symbols, and mediums, hybrid text provides an optimum environment not only for the delivery of meaning but the sharing of the subject``s experiences and thinking process. The three types of expression . combined, latent, transfigured - allows hybrid text to acquire an authenticity in the delivery of meaning by its ability for realistic and immediate recreation using the combination of synesthesia, symbols, and mediums. The interest in and study of hybrid text has resulted in an area of research that allows one to explore both our sensual aesthetic experiences and intellectual activities based on human senses at the same time. This area of research can also perform the role of connecting various fields of study. In terms of design education, the study of hybrid texts allows the simultaneous exploration of various areas of design, semiotics processes, and mediums. Further study of hybrid text will contribute in the formation of a systematic framework for understanding human experiences in the digital media environment and for developing a more human-centered design.